Fatty acid profiles and antioxidants of organic and conventional milk from low‐ and high‐input systems during outdoor period. (23rd July 2014) - Kusche, Daniel; Kuhnt, Katrin; Ruebesam, Karin; Rohrer, Carsten; Nierop, Andreas FM; Jahreis, Gerhard; Baars, Ton
Abstract BACKGROUND Intensification of organic dairy production leads to the question of whether the implementation of intensive feeding incorporating maize silage and concentrates is altering milk quality. Therefore the fatty acid (FA) and antioxidant (AO) profiles of milk on 24 farms divided into four system groups in three replications (n = 71) during the outdoor period were analyzed. In this system comparison, a differentiation of the system groups and the effects of the main system factors 'intensification level' (high‐input versus low‐input) and 'origin' (organic versus conventional) were evaluated in a multivariate statistical approach. RESULTS Consistent differentiation of milk from the system groups due to feeding‐related impacts was possible in general and on the basis of 15 markers. The prediction of the main system factors was based on four or five markers. The prediction of 'intensification level' was based mainly on CLA c9, t11 and C18:1 t11, whereas that of 'origin' was based on n‐3 PUFA. CONCLUSION It was possible to demonstrate consistent differences in the FA and AO profiles of organic and standard conventional milk samples. Highest concentrations of nutritionally beneficial compounds were found in the low‐input organic system. Adapted grass‐based feeding strategies including pasture offer the potential to produce a distinguishable organic milk product quality. © 2014 Society of Chemical Industry